2019
DOI: 10.1515/jpem-2018-0512
|View full text |Cite
|
Sign up to set email alerts
|

Testicular adrenal rest tumors in patients with congenital adrenal hyperplasia: 6 years of follow-up

Abstract: Background Testicular adrenal rest tumors (TARTs) leading to primary gonadal failure are the main etiology of infertility in congenital adrenal hyperplasia (CAH). We aimed at identifying the evolution of TART and related findings in young CAH patients. Methods Twelve male patients (3–23 years old) with 21-hydroxilase deficiency (11 with classic salt-wasting form) were included. Testicular ultrasonography (US) was performed in two moments, by a single blinded specialist in pediatric diagnostic imaging. Tumor p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Unsupervised hierarchical clustering using the complete clustering method showed that TART was most similar to either adult (adrenal-and testis) tissue, and least similar to either fetal (adrenal and testis) tissue ( Figure 2A). Ten TART samples (TART1-5,8-12) from CAH patients and two TART samples that were removed from a patient with Cushing's Disease (Cushing-TART (CT)) were clustered together with adult adrenal tissue, whereas four TART samples (TART6, 7,13,14) were clustered together with adult testis tissue. Fetal adrenal and testis tissues were clustered separately.…”
Section: Transcriptome Of Tart Is Most Similar To Adult Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Unsupervised hierarchical clustering using the complete clustering method showed that TART was most similar to either adult (adrenal-and testis) tissue, and least similar to either fetal (adrenal and testis) tissue ( Figure 2A). Ten TART samples (TART1-5,8-12) from CAH patients and two TART samples that were removed from a patient with Cushing's Disease (Cushing-TART (CT)) were clustered together with adult adrenal tissue, whereas four TART samples (TART6, 7,13,14) were clustered together with adult testis tissue. Fetal adrenal and testis tissues were clustered separately.…”
Section: Transcriptome Of Tart Is Most Similar To Adult Tissuesmentioning
confidence: 99%
“…ACTH is considered to be a growth promoting factor of TART, as the growth of TART is associated with poor hormonal control (11) and correlates with increased ACTH levels (12,13). Besides, intensifying glucocorticoid treatment is sometimes effective in reducing tumor size, most likely due to the suppressing effects on ACTH levels (12,(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Reported prevalence of TARTs varied between 14% to 86% in the literature. [1][2][3][4][5][6][7][8][9][10][11] This variation is related to age range of the patient population, the severity of the disease and the method of detection. In studies included only children, the prevalence was reported between 10% to 70%.…”
Section: Discussionmentioning
confidence: 99%
“…1,19 In poorly controlled patients with CAH, high ACTH levels cause proliferation of undifferentiated adrenal cells which induces the formation of TART in rete testis. 3 Optimization of steroid treatment is recommended to prevent disease progression. However, suppression of ACTH secretion is not always successful in reducing tumor size, and even well-controlled CAH patients with normal or suppressed plasma ACTH levels have testicular adrenal resting tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation